2013
DOI: 10.1074/jbc.m112.431536
|View full text |Cite
|
Sign up to set email alerts
|

Functional Separation of Endosomal Fusion Factors and the Class C Core Vacuole/Endosome Tethering (CORVET) Complex in Endosome Biogenesis

Abstract: Background:The interdependence of the endosomal fusion factors CORVET and Vac1 has not been addressed. Results: CORVET can be separated from other endocytic fusion factors on the basis of ultrastructure, localization, and trafficking. Conclusion: CORVET acts independently of the Vac1 tether and requires activated Rab5 homologs for localization. Significance: Our data reveal a unique role of CORVET in sorting of biosynthetic cargo to the vacuole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 56 publications
5
78
0
Order By: Relevance
“…2A). For Vps21, it was shown recently that two GEFs, Vps9 and Muk1, act redundantly (33,34). In agreement with this, only the dual deletion of both GEFs resulted in redistribution of Vps21 to the ER among…”
Section: Rab Gtpases Are Mislocalized In the Absence Of Their Gefs Orsupporting
confidence: 64%
“…2A). For Vps21, it was shown recently that two GEFs, Vps9 and Muk1, act redundantly (33,34). In agreement with this, only the dual deletion of both GEFs resulted in redistribution of Vps21 to the ER among…”
Section: Rab Gtpases Are Mislocalized In the Absence Of Their Gefs Orsupporting
confidence: 64%
“…In agreement with this, it has been found that purified CORVET is able to tether efficiently vacuole-associated endosomes in a Rab5/Vps21-dependent manner both in vitro and in vivo (Balderhaar et al, 2013). Endosomal fusion and fission appear to be crucial for the generation of MVBs and protein sorting as Rab5 mutants are defective in both processes (Cabrera et al, 2013;Nickerson et al, 2012;Russell et al, 2012). Indeed, the generation of an average MVB of a radius of 100 nm that carries up to 50 intraluminal vesicles (Luhtala and Odorizzi, 2004) would require several fusion events to provide sufficient membrane for the vesicle generation.…”
Section: Box 1 the Functions Of Rab5 And Rab7 Within The Endolysosommentioning
confidence: 51%
“…Interestingly, all class D genes encode proteins involved in membrane fusion at endosomes (Bowers and Stevens, 2005). Recently, it was shown that the CORVET subunits have a function that is distinct and possibly downstream from Vps45 and Vac1 (Cabrera et al, 2013), which also binds Vps21-GTP (Peterson et al, 1999;Tall et al, 1999). The CORVET subunits Vps3 and Vps8 localize independently of Vac1, Vps45 and Pep12 but still require activated Rab5 proteins for their localization and function (Cabrera et al, 2013).…”
Section: Box 1 the Functions Of Rab5 And Rab7 Within The Endolysosommentioning
confidence: 99%
See 2 more Smart Citations